Periorbital swelling: the important distinction between allergy and infection. Issue 2 (26th February 2004) - Goodyear, P W A; Firth, A L; Strachan, D R; Dudley, M
Abstract : Orbital cellulitis and abscess formation are rare complications of sinusitis, however acute orbital inflammation is secondary to sinusitis in about 70% of cases. Delay in diagnosis must not occur to avoid serious complications such as blindness and life threatening intracranial sepsis. A case is reported in which despite late referral, emergency surgical intervention was sight saving.